Potential Maternal Risk Factors for Low Birth Weight in Indonesia: A Systematic Review - Nurwati, Yuni; Hardinsyah, Hardinsyah; Marliyati, Sri Anna; Santoso, Budi Iman; Anggraini, Dewi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This review was conducted with the aim of summarizing the articles on the potential maternal risk factors for Low Birth Weight (LBW) in Indonesia. All observational studies conducted in Indonesia between 2010 and 2022 were thoroughly reviewed in this study. The articles were retrieved from